Analysis Of The Application Of Integrated Learning Type Connected In Ips Subjects To Improve Learning Outcomes Of Grade IV Elementary School Students - Hudi Basuki; Waspodo Tjipto Subroto; Wahyu Sukartiningsih (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2025)
This study aims to analyze the impact of connected type integrated learning approach to improve learning outcomes of fourth grade students in social studies subject. The connected type integrated learning approach allows students to connect various concepts in learning materials, thus improving their understanding and learning outcomes. This study used a quantitative method that was designed with experiments and utilized initial and final tests to determine changes in student learning outcomes. The research findings revealed a significant increase in student learning outcomes, with the initial average score of 66.97 rising to 83.03 on the posttest, showing an increase of 24.45% of the total population. In addition to the average score, student involvement in the learning process also increased from 61, 68% to 85, 33%. Based on the above results, it can be concluded that the application of a connected type integrated learning approach is effective in improving student learning outcomes in social studies subjects at SDN 3 Baron, Baron District, Nganjuk Regency. Therefore, this method is recommended to be applied consistently to improve the quality of education and student learning outcomes in elementary schools.